KEBIJAKAN PENGELOLAAN LIMBAH ELEKTRONIK DALAM LINGKUP GLOBAL DAN LOKAL = Electronic Waste Management Policies in the Scope of Global and Local - Wahyono, Sri (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2013)
In line with population growth and lifestyle, the number of electronic waste increased. Electronicwaste is a hazardous waste that threaten human survival. Various efforts have been and are beingtaken to prevent environmental degradation caused by poor management of electronic waste.However, electronic waste is a source of valuable material that can be recovered through a series ofprocesses in the manufacturing of electronic waste. Support from various parties necessary for therealization of a sustainable e-waste management.Keywords: electronic waste, pollution, extended producer responsibilityAbstrakSejalan dengan pertumbuhan penduduk dan gaya hidup, limbah elektronik semakin meningkatjumlahnya. Limbah elektronik secara umum merupakan limbah berbahaya sehingga dapatmengancam kelangsungan hidup manusia. Berbagai upaya telah dan sedang dilakukan untukmencegah terjadinya degradasi lingkungan akibat pengelolaan limbah elektronik yang buruk. Namundemikian, limbah elektronik adalah sumber material berharga yang dapat di-recovery melaluiserangkaian proses di industri pengolahan limbah elektronik. Dukungan dari berbagai pihakdiperlukan untuk terwujudnya pengelolaan limbah elektronik yang berkelanjutan.Kata Kunci: Limbah elektronik, pencemaran, extended producer responsibility